PENGARUH EFEKTIVITAS APLIKASI SISTEM INFORMASI ABSENSI PEGAWAI TERHADAP KEDISIPLINAN PEGAWAI - Tsana Qotrunnada Oktariani; Dian Purwanti; Andi Mulyadi (LPPM Universitas Djuanda Bogor, 2021)
ABSTRACTResearch on Employee Attendance Information System Applications (SIAP) on this discipline is motivated by1) low level of employee discipline relating to attendance and punctuality at work, 2) easy application to be manipulated by employees, 3) frequent system disturbances (errors) in the application when used by employees, which have an impact on the ineffectiveness of the SIAP system. Research analysis using Information Systems theory from Davis and Discipline Theory from Singodimedjo.The method used is quantitative with associative models. Respondents were civil servants in the Regional Secretariat of Sukabumi, totaling 160 people. 61 samples were taken using proportionate stratified random sampling technique. The results of data analysis showed a correlation coefficient of 0.918. The coefficient of determination is 84.3%. For this reason, researchers suggest that the local government of Sukabumi City improve the accuracy of the SIAP attendance system by adding a face camera system.Keywords: SIAP Application, Face Camera, Discipline, Information System